2021
DOI: 10.1292/jvms.20-0338
|View full text |Cite
|
Sign up to set email alerts
|

Association between antimicrobial treatment and resistance of pathogenic <i>Escherichia coli</i> isolated from diseased swine in Kagoshima Prefecture, Japan

Abstract: Pathogenic Escherichia coli is an important cause of diarrhea, edema disease, and septicemia in swine. In Japan, the volume of antimicrobial drugs used for animals is highest in swine, but information about the prevalence of antimicrobial-resistant bacteria is confined to apparently healthy animals. In the present study, we determined the O serogroups, virulence factors, and antimicrobial resistance of 360 E. coli isolates from swine that died of disease in Kagoshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…The use of ceftiofur was not only associated with amoxicillin and cefotaxime resistance but also with structurally unrelated antimicrobials such as chloramphenicol [ 45 ]. In this study, resistance to chloramphenicol was observed in 35 isolates of piglets (58.33%), despite no phenicols being used in the early stages of the piglets’ lives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of ceftiofur was not only associated with amoxicillin and cefotaxime resistance but also with structurally unrelated antimicrobials such as chloramphenicol [ 45 ]. In this study, resistance to chloramphenicol was observed in 35 isolates of piglets (58.33%), despite no phenicols being used in the early stages of the piglets’ lives.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, resistance to chloramphenicol was observed in 35 isolates of piglets (58.33%), despite no phenicols being used in the early stages of the piglets’ lives. Indeed, in previously reported studies, chloramphenicol resistance genes have often been found on the same ESBL encoding plasmids [ 45 , 46 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of livestock also plays an important role in the dissemination of this bacteria to the environment and could be the main link in the contamination route to collared peccaries. There is evidence of domestic animals acting as carriers of strains of DEC mainly cattle (Gutema et al, 2021), sheep, and goats (Shabana & Al-Enazi, 2020), birds (Kimura et al, 2021) and pigs (Misumi et al, 2021). In Mexico, DEC strains have been reported in humans and animals (Rivas-Ruiz et al, 2020;Tamayo-Legorreta et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, more than half of the DEC strains were not susceptible to at least one antibiotic from three different categories tested (MDR), mainly beta-lactams, aminoglycosides, cephalosporins, fluoroquinolones and nitrofurantoin. Resistance to beta-lactams such as ampicillin was observed in DEC isolated from canaries (Kimura et al 2021), pigs (Misumi et al, 2021) and bovines, cow meat and humans (Gutema et al, 2021). In Mexico, multidrug resistant E. coli infections are a common occurrence, and the incidence of DEC strains resistant mainly to ampicillin and tetracycline has been reported in bovine faeces (Navarro et al, 2018), beef and pork (Martínez-Vázquez et al, 2018), as well as in humans (Castro et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-seven other fecal samples excreted in the environment were collected from piglet houses. All samples used in this study had been checked in advance for the presence or absence of stx2e-positive E. coli by the suppliers using DHL agar and blood agar plates [9] and subsequently conducting PCR for the stx2e gene [11]. Information about each sample used in this study is shown in Supplementary Table 1.…”
Section: Preparation Of Test Samplesmentioning
confidence: 99%